Learning to Lead: 3 Models to Support Public Health Leadership Development. (September 2022) - Brandert, Kathleen; Alperin, Melissa; Lloyd, Laura M.; Rose, Barbara; Bekemeier, Betty; Rogers, Megan; Grimm, Brandon
Abstract : Context: The current public health system is underresourced and understaffed, which has been exacerbated by the coronavirus pandemic. In addition, there has been a decline in the public health workforce at both state and local levels during the last decade. While workforce numbers dwindle, public health systems have to address increasingly complex challenges—such as climate change, chronic diseases, and health equity—challenges that require skilled, adaptive leaders. This article describes the importance of leadership development and how 3 public health training centers (PHTCs) are building leadership skills in the public health workforce. Program: To address the need for public health leadership training, the PHTCs in the Health & Human Services (HHS) Regions 4, 7, and 10 all offer public health leadership institutes (PHLIs). Implementation: The 3 PHLIs discussed in this article vary in longevity (3-18 years), cohort length (8-12 months), and format (virtual, in-person, and hybrid); yet, all 3 emphasize adaptive leadership through a health equity lens and intentional opportunities to apply skills in practice. Evaluation: Each PHLI conducts extensive evaluation based on Kirkpatrick's levels of evaluation and collects common metrics collected by all PHTCs. Data from the PHLIs illustrate high levels of satisfaction with learning, presentation of data, identification of workplace actions, and improvement of subject matter understanding. Each PHLI also has numerous stories of impact. Discussion: With public health leaders leaving the workforce and the complexities of practice increasing, leadership training is critical to the current workforce and succession planning. These PHTCs provide a significant, enduring resource toward the development of our nation's public health leaders, as well as meeting the unique needs of their regions' workforces.